La corrida, un imaginaire national genré au service de la régénération (Espagne, 1895-1923) - David Castro Devesa (Genre & Histoire)
The objective of this article is to analyze the discourses linking bullfighting shows to the construction of the nation and to gender identities in Spain between 1895 and 1923. This period covers a moment of national crisis in Spanish history and the reconfiguration of the roles of male and female in society. To do so, this research explores these issues through three relevant examples : the success of a team of women bullfighters, the Noyas; the transsexuality of a bullfighter, the Reverte; and the famous rivalry between two bullfighters, Joselito and Belmonte. This article approaches the trajectories of each case through analysis of articles in the generalist and the bullfighting press, identifying journalists’ discursive practices on both nation and gender, in close connection with the evolution of Spanish society and its system of cultural representations of national and gender identities.